Pengembangan Budidaya Lebah Kelulut Di Desa Batu Tanam, Sambung Makmur, Kabupaten Banjar, Kalimantan Selatan - Wiwin Tyas Istikowati; Sunardi Sunardi; Muhammad Arief Soendjoto; Syaifuddin Syaifuddin (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2019)
The aim of this community service in Batu Tanam village was to develop stingless beekeeping that was started in 2016 to be the village main program. The program was the socialization of the potential of stingless beekeeping, planting of the several types of flowers in the activity location, and the additional number of bee boxes managed by villagers. From this activity, the community has recognized the potential of stingless beekeeping and Batu Tanam village will make this program be the main program in village innovation activities.